2012
DOI: 10.1134/s102279541201005x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of gene HSM3 with genes of the epistatic RAD6 group in yeast Saccharomyces cerevisiae

Abstract: In eukaryotes, damage tolerance of matrix DNA is mainly determined by the repair pathway under the control of the RAD6 epistatic group of genes. This pathway is also a main source of mutations gen erated by mutagenic factors. The results of our recent studies show that gene HSM3 participating in the con trol of adaptive mutagenesis increases the frequency of mutations induced by different mutagens. Mutations rad18, rev3, and mms2 controlling various stages of the RAD6 pathway are epistatic with mutation hsm3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…According to our research and the data presented in work [38], in the double hif1∆ rad52∆ and hsm3∆ rad52∆ mutants, hif1∆ and hsm3∆ mutants were equally epistatized to recombination-deficient mutants. These data support the hypothesis advanced earlier that hsm3∆ mutation (maybe hif1∆) leads to the destabilization of the D-loop during the post-replicative repair [38,43] and thus reduces the load on the path of the recombination repair, which is blocked in rad52∆ mutant. To further test the survival of hsm3∆ and hif1∆ mutants, we performed experiments with UV light.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…According to our research and the data presented in work [38], in the double hif1∆ rad52∆ and hsm3∆ rad52∆ mutants, hif1∆ and hsm3∆ mutants were equally epistatized to recombination-deficient mutants. These data support the hypothesis advanced earlier that hsm3∆ mutation (maybe hif1∆) leads to the destabilization of the D-loop during the post-replicative repair [38,43] and thus reduces the load on the path of the recombination repair, which is blocked in rad52∆ mutant. To further test the survival of hsm3∆ and hif1∆ mutants, we performed experiments with UV light.…”
Section: Resultssupporting
confidence: 89%
“…Earlier in our laboratory, extensive research was carried out on the genetic properties of hsm3Δ mutation [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. We have shown that proteins Mms2, Xrs2, Srs2, Mph1, Mms4, involved in the error-free branch of the PRR, have a crucial function in hsm3 -dependent UV mutagenesis [ 38 , 43 ]. These results strongly suggest that the HSM3 gene is involved in the error-free branch of damage bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier analysis of the genetic interactions of the hsm3 mutation with mutations blocking three differ ent repair pathways showed that the HSM3 gene is involved in postreplicative (RAD6 dependent path way) and recombination (RAD52 dependent pathway) repair [7,29]. It was assumed that the mutator pheno type of the hsm3 strain is determined by processes tak ing place in the D loop.…”
Section: Discussionmentioning
confidence: 99%
“…A domain responsible for mutagenesis is in the region of last amino acid residues of the protein [6]. The rad18, rev3, and mms2 muta tions, which control different steps of the RAD6 path way display epistatic interactions with the hsm3 muta tion, reducing the level of UV induced mutagenesis to a level characteristic of single radiation sensitive mutants [7]. The results allowed us to conclude that the mutator phenotype of the hsm3 strain may be determined by processes taking place in the D loop.…”
Section: Introductionmentioning
confidence: 99%
“…S. cerevisiae strains used in this work are described in Table 1 . The xrs2Δ (2ETA-3031) mutant were obtained from the previously described 11D-3031 ( MATα ade2Δ-248 leu2-3,112 ura3-160,188 trp1 ) strain by gene replacement (Fedorova et al 2004 ; Chernenkov et al 2012a , b ). The 11D-3031 strain was transformed with modules, and the transformants were selected on plates with YEPD containing 30 mg/l nourseothricin and on plates with selective media without uracil, respectively.…”
Section: Methodsmentioning
confidence: 99%